Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.2 - More Work with Exponents and Scientific Notation - Exercise Set - Page 268: 44



Work Step by Step

$(\frac{8^{-3}}{y^{2}})^{-2}$ Using $\frac{1}{a^{n}}= a^{-n}$ $= (8^{-3}y^{-2})^{-2}$ $= (8^{-3})^{-2}(y^{-2})^{-2}$ Using $(a^{m})^{n} =a^{m \times n} $ $=8^{6}y^{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.